Fatigue Behavior of Dissimilar Aluminum Alloy Spot Welds. (2015) - Kang, Jidong; Chen, Yuhua; Sigler, David; Carlson, Blair; Wilkinson, David S.
Abstract: With the broader utilization of a variety of aluminum alloys in the automotive industry for structural lightweight applications, the need for resistance spot welding (RSW) of dissimilar aluminum alloys is increasing. General Motors (GM) has developed a proprietary RSW process using a multi-ring, domed electrode geometry that significantly improves the performance of the aluminum resistance spot welds. In addition, to enhance structural performance, epoxy adhesivesare also often applied prior to RSW to obtain weld-bonded joints. As a contribution, the load-controlled fatigue behavior of dissimilar aluminum alloy spot welds made of 2 mm thick AA5754 wrought sheet and 3 mm thick Aural2 die casting sheet with and without the addition of adhesive prior to welding was studied. The same GM proprietary resistance spot welding electrode and current schedule was applied to both welding conditions leading to a larger nugget size when using adhesive, but both weld configurations presented similar maximum load in tension-shear testing. X-ray computed tomography was used to detect internal welding discontinuities such as voids and also to follow the damage evolution and fatigue crack initiation and growth during interrupted fatigue testing of the spot welds. The results show that the main fatigue crack initiates at the edge of the nugget and penetrates through the Aural2 die casting sheet in the thickness direction. Using the structural stress concept, it was also found that the structural stress-fatigue life curve for AA5754 to Aural2 aluminum spot welds with and without adhesive falls into a master curve indicating that the nugget size which corresponds to the tensile and bending strength dominates fatigue life.